Effect of Sound Source Location and Spatial Hearing on the Vestibulo-Ocular Reflex - Easterday, Mary; Plyler, Patrick N; Doettl, Steven M; Johnstone, Patti; McCaslin, Devin (Journal of the American Academy of Audiology)
Background: There have been conflicting results on the effect of auditory stimulation on the vestibulo-ocular reflex (VOR) with some studies indicating suppression, enhancement, or no effect. No studies to date have assessed the effect of sound source location on VOR gain or the relationship between spatial hearing ability and VOR gain. Purpose: The purpose of the present study was to determine if VOR gain was affected by moving the location of the sound source within participants and to determine if these effects were related to spatial hearing ability. Research Design: A between subjects repeated measures experimental design was utilized. Study Sample: Two groups of participants (adult and child) with normal otologic, vestibular, and neurologic function. 22 adults (20 female and 2 male; average age = 23 years) and 16 children (9 female and 7 male; average age = 7.5 years) were included in data analysis. Data Collection and Analysis: VOR gain was measured using rotational chair stimulation in the following auditory conditions: silent, insert earphones, external loudspeaker at 0° azimuth rotating with participant, and external stationary speaker. Localization ability was measured using root mean square (RMS) error. Results: Results indicated a significant effect for sound source location on VOR gain and VOR difference gain in both groups. RMS error was positively correlated for the moving and fixed sound source locations for both adults and children. Conclusion: VOR gain was significantly affected by location of the sound source. Findings suggest the presence and location of an auditory stimulus during rotational testing can alter results during the assessment.